In vitro activity of levofloxacin against lower respiratory tract pathogens - Sarkar, Soma (J Basic Clin Pharm, 2015)
BACKGROUND: Considerable morbidity and mortality are associated with lower respiratory tract infections (LRTIs) that put a considerable strain on the health budget. Selection of appropriate antibiotics as empirical therapy maximizes positive patient outcomes, and that depends on regular surveillance of infective agents and their antibiograms, which vary according to the geographical areas. AIM: The aim was to study the drug susceptibility pattern of the isolated pathogens of the respiratory tract infections. SETTINGS AND DESIGN: Retrospective study for a period of 1-year 3 months from January 2013 to March 2014 at a Tertiary Care Hospital. MATERIALS AND METHODS: Eleven hundred and eighty-four sputum samples from both outdoor and indoor patients with symptoms of LRTI were processed, and antibiotic sensitivity test was done to commonly used antibiotics. Descriptive statistics was used to analyze the data. RESULTS: Among 502 quality sputum samples, 312 (62.15%) samples showed growth of pathogenic bacteria. The most common pathogens were Klebsiella spp. (38.14%), Moraxella spp. (16.02%), Streptococcus pneumoniae (14.10%), Pseudomonas spp. (9.93%), S. aureus (9.29%). It was found that the overall susceptibility pattern was <50% for amoxicillin, amoxicillin-clavulanic acid, cefuroxime, cotrimoxazole and erythromycin whereas for cefotaxime, cefixime, and cefoperazone-sulbactum it was 60.08%, 51.59%, 69.04%, respectively. The susceptibility to ciprofloxacin, ofloxacin, and levofloxacin were 66.67%, 70.19% and 83.33%, respectively. CONCLUSION: Klebsiella spp. was the most common LRTI pathogen. There was limited activity of amoxicillin, amoxicillin-clavulanic acid, cefuroxime, cotrimoxazole and erythromycin for the treatment of LRTI whereas levofloxacin, (being an oral drug with good compliance) had good activity against respiratory pathogens and could be used for empiric treatment in LRTI.